Combining accessibilities for different activity types: Methodology and case study - Lijuan Zheng; Bert van Wee; Markus Oeser (Journal of Transport and Land Use)
Accessibility is a key concept in transport planning. Most studies only focus on specific activity types, but for policy making it is more relevant to aggregate accessibility overall or at least several activity types. However, to the best of our knowledge, there is no study that combines accessibilities for different activity types. Since access to spatially separated activities is one dimension of quality of life, and activity types are not equally important for quality of life, we propose a methodology that is based on weighing activity types according to their relative importance to quality of life to assess overall accessibility. Four principles are adopted to develop the weighting factors: 1) the human needs the activity types satisfy; 2) the activity types' contribution to quality of life; 3) the activity types' trip frequency; 4) further modifications, based on principles such as whether the activity types are needed in emergent situations, and social values and policy preferences. We combine these four principles and apply the methodology in a case study focused on Germany.